Legal Protection of Vulnerable Persons - Marcheva, Deyana (Yearbook of the Law Department, 2021)
In this article I discuss the issue how the law should define the vulnerable persons and whether the approach should be categorial or contextual. I argue that it is impossible in advance to make a list of all categories of vulnerable persons or groups in all possible legal contexts and for this reason the theory of vulnerable subject should not be ignored. The principles of rule of law, equality and human rights protection require for considering the specific situation of vulnerable persons in all administrative and court procedures so that they will benefit from more extensive and reinforced procedural protection of their rights. Such a procedural standard needs to be applied everywhere whether or not the legal framework provides for special statute of the persons from vulnerable groups, as in the Asylum and Refugees Act.